Novel coaxial transition for shaped coaxial horn antennas operating at millimeter wave frequencies - Simionato, E. [UNESP]; Zang, Sandro R.; Aldaya, Ivan [UNESP]; De Oliveira, José A. [UNESP]; Rosa, Guilherme S.; Penchel, Rafael A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work presents a novel optimized design and analysis of a coaxial coupling structure for standard and shaped horn antennas operating at millimeter wave frequencies. A novel dielectric support structure for the inner conductor and a transition to a 2.92 mm K connector are proposed. The horn's performance was evaluated through full-wave electromagnetic finite element method analysis performed on Ansys EM. The dimensions of the dielectric structure and transition were optimized using a multi-objective Genetic Algorithm to enhance the horn's performance. The final design presented a frequency bandwidth greater than 45% (25-40 GHz) with a return loss exceeding 20 dB.